Radon Therapy Is Very Promising as a Primary or an Adjuvant Treatment for Different Types of Cancers: 4 Case Reports - Shuji Kojima; Jerry M. Cuttler; Kiyomi Inoguchi; Kenshou Yorozu; Takashisa Horii; Noriko Shimura; Hironobu Koga; Akihisa Murata (SAGE Publishing, 2019)
We report on the application of radon inhalation therapy to patients with 4 types of cancer: colon, uterine, lung, and liver cell. The radon treatments were given to improve the efficacy of chemotherapy and were potent in all 4 cases. Marker values decreased and disease symptoms were alleviated. We include a lengthy discussion on the mechanism that may be responsible for the observed results. While employing the radon generator to treat the patient with hepatocellular carcinoma, we discovered that a concentration of 6 MBq/m 3 was very effective, while 1 MBq/m 3 was marginal. This implies different, and rather high, radon concentration thresholds for the treatment of different types of cancer. The evidence from these 4 cases suggests that radon inhalation may be beneficial against various cancer types as an important adjuvant therapy to conventional chemotherapy and for local high-dose radiotherapy, which would address the problem of distant metastasis. A previous case report on 2 patients with advanced breast cancer, who refused chemotherapy or radiotherapy, indicates that radon may be effective as a primary therapy for cancer. Clinical trials should be carried out to determine the best radon concentrations for treatment of other types of cancer, at different stages of progression.